Pelatihan Akreditasi Jurnal Nasional Bagi Pengelola Jurnal se Indonesia di Universitas Pelita Bangsa, Cikarang, Bekasi - Syamruddin Syamruddin; Gatot Kusjono; Iman Lubis; Oki Iqbal Khair; Andi Sopandi (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
This Community Service (PkM) aims to share and share knowledge and enlightenment for journal managers in Indonesia on how to manage journals properly and correctly. Then provide tips on preparing for an accredited journal. Besides that, it also helps journal managers to achieve the National Journal Accreditation (Arjuna) SINTA. The methods used are in the form of orientation, lectures, workshops, journal reviews, and evaluations. The method consists of four stages, namely pre-training, training, post-training, and continuous PkM activities. The results obtained by the participants during the training were that they increasingly understood how to manage a good and correct journal. Participants know how to manage journals through open-access journals using open journal systems. Furthermore, after understanding the correct management of journals, participants are more confident in preparing their journals for national journal accreditation. The next stage, is ready to register the journal to be accredited by the National Research and Innovation Agency (BRIN).